Identifying conflicts tendency between nature-based tourism development and ecological protection in China. (February 2020) - Yuxi, Zeng; Linsheng, Zhong
Highlights: We propose ICTP to coordinate between tourism development and ecological protection. Areas with higher ICTP are more prone to nature-based tourism vs. ecological protection conflicts. Considerable proportion of studied areas (ca. 13.79%) have very high ICTP. These areas are characterized with both high landscape attractiveness and high ecological sensitivity. Abstract: Developing spatial regulation strategies is important for nature-based tourism, and this procedure could be more rational and scientific with the understanding of the spatial distribution of conflicts tendency between tourism development and ecological protection. In this study, we developed an Indicator of Conflict tendency between nature-based Tourism development and ecological Protection (ICTP), based on the combination of landscape attractiveness and ecological sensitivity. By integrating land cover, topography, climate and other datasets, this paper presents the spatial distribution of the ICTP in the study area in China. The results show that most areas of China have a low or medium ICTP. Areas with very high ICTP account for 13.79% of the studied areas, including the central part of the Inner Mongolia Plateau, northern part of the Loess Plateau, southwestern part of the Northeast Plain, north and south sides of Tianshan Mountains, coast of Bohai Bay and coastal areas of Jiangsu and Zhejiang Province. These areas are mainly confronted with problems of desertification, salinization and soil erosion. 11.09% of studied areas have very low ICTP, mainly located in the Tarim Basin and western part of Inner Mongolia Plateau, characterized by low landscape attractiveness and low ecological sensitivity. Our results can inform decision makers with regard to where are most likely to suffer from ecological problems caused by nature-based tourism activities, and to which types of problems that are likely to arise. Such information can help decision makers forecast the developmental trend of the relationship between nature-based tourism development and ecological protection, further determine the degree of control on nature-based tourism. The study developed the basic framework for measuring the conflict tendency of nature-based tourism development and ecological protection, which can inspire researchers to think about factors that should be considered when measuring such tendency.